Analysis of the Dynamic Capabilities of Sidoarjo SME in Improving the Performance of Sustainable Innovation - Bima Prasetya, Miftaqul; Muzdalifah , Laily; Novie , Muhafidhah; Sholikhah , Afifatus (Manunggal Halim Jaya, 2026)
This study analyzes the role of four dimensions of dynamic capabilities: Perceptual Ability, Analytical Competence, Unification Expertise, and Harmonization Capacity in encouraging Sustainable Innovation Performance in SMEs in Sidoarjo Regency. A quantitative approach with a sample of 121 SMEs showed that Harmonization Capacity had a positive and substantial influence on sustainable innovation performance. In contrast, Analytical Competence and Coordination Capacity showed a significant positive effect. In contrast, Integration Capabilities did not show a significant influence. These findings underscore the importance of the learning process and strategic coordination in increasing the sustainable innovation capacity of Sidoarjo SMEs, with practical implications for the development of supporting policies and strengthening the managerial capabilities of local SMEs.